2003
DOI: 10.1021/la035834k
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic Fluorinated Surfactant: Investigation of Phase Diagram and Preparation of Ordered Mesoporous Materials

Abstract: The behavior of fluorinated surfactant F(CF2)8C2H4(OC2H4)9OH in water solution was investigated, and the preparation ofmesoporous molecular sieves was achieved. A direct micellar phase (L1) and a hexagonal (H1) liquid crystal were found. Small-angle X-ray scattering measurements proved that the hydrophobic chains are completely extended and that the cross sectional area remains constant in H1. At 80 degrees C, materials with a hexagonal array of their channel are prepared via a cooperative templating type mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 41 publications
7
91
1
Order By: Relevance
“…This observation led us to conclude that the CTM mechanism is not favored if the cloud point is too low. This tendency is confirmed by the investigation of the R F 8 (EO) 9 /water system [31], since for this surfactant the value of cloud point is superior to 100 • C and we have demonstrated that without oil well ordered materials can be obtained.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This observation led us to conclude that the CTM mechanism is not favored if the cloud point is too low. This tendency is confirmed by the investigation of the R F 8 (EO) 9 /water system [31], since for this surfactant the value of cloud point is superior to 100 • C and we have demonstrated that without oil well ordered materials can be obtained.…”
Section: Discussionsupporting
confidence: 75%
“…Taking into account this equivalence rule, we can consider that C 16 (EO) 10 is the hydrogenated analogue of R F 8 (EO) 9 . Indeed, both templates have the same V H /V L ratio equal to 1.4 and lead to well ordered mesoporous materials [15,31]. Therefore, if V H /V L is the main parameter that drives the channel arrangement, using R F 7 (EO) 7 (V H /V L = 1.1) we could expect to form well ordered mesostructures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monduzzi et al reported the counterion effect on the phase behavior of perfluropolyether carboxylates in water [12][13][14]. In spite of the growing study of phase behavior of nonionic fluorinated surfactants in water [15][16][17][18][19][20], the incorporation of fluorinated oil into self-organized structures of fluorocarbon surfactant has rarely been considered [21]. Perfluoropolyether (PFPE) oils have been used as lubricants in many industrial applications and possess the main properties of fluorinated surfactants like thermal, chemical, and biological inertness, and low compatibility with aqueous and hydrocarbon based systems.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in shape suggests a decline in pore regularity. The observed phenomena are characteristics of wormhole-like architectures [4,6,[12][13][14][15] . We found that it is especially so in the cases of the EG-removed CZY precursor and the CZY-3 sample (curves 3 and 4 in Figure 3(a)); the latter case may be related to the partial occupancy of NaCl inside the pores of the CZY precursor.…”
Section: Crystal Phase Structurementioning
confidence: 99%